Phycocyanin production from Galdieria sulphuraria 009 in palm oil mill effluent: growth, extraction, and antioxidant activity: Produksi fikosianin dari Galdieria sulphuraria 009 dalam limbah cair pabrik kelapa sawit: pertumbuhan, ekstraksi, dan aktivitas antioksidan - Rahman, Delicia Yunita; Praharyawan, Swastika; Apriastini, Marsiti; Nurcahyani, Puji Rahmawati; Nafisyah, Ayu Lana; Fatriasari, Widya; Amrullah, Apip; Farobie, Obie (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Palm oil mill effluent (POME), a major byproduct of the palm oil industry in Indonesia, is generated in large volumes and poses environmental risks due to its high organic content> Microalgae offer a promising approach to reduce this waste while simultaneously producing value-added biomass products. This study aimed to determine the optimal POME concentration for microalgal growth of G. sulphuraria 009, to evaluate phycocyanin yield, and to assess its antioxidant activity. This study was initiated with a preliminary screening using 5–50% POME to identify optimal microalgal growth conditions; cultivation in bioreactors with selected concentrations (2.5%, 5.0%, and 7.5%) to evaluate growth performance and chemical yields; and analysis of antioxidant activity and pigment content in both fresh and residual biomass. The preliminary stage revealed 5% POME as the upper threshold for growth, with 2.5% supporting optimal biomass comparable to control (Allen pH 2). Higher POME levels inhibited growth due to light attenuation and ammoniacal nitrogen toxicity. 2.5% POME recorded the highest phycocyanin yield per liter, while 7.5% POME yielded the highest antioxidant activity, likely due to oxidative stress. Antioxidant assays confirmed significant antioxidant activity in all phycocyanin extracts, with the highest activity in 7.5% POME, likely due to oxidative stress. Carotenoid and chlorophyll contents were evaluated in both fresh and residual biomass. Carotenoids were more abundant in fresh biomass, while chlorophyll -A was higher in residual biomass post-extraction, emphasizing the importance of extraction techniques in bioactive compound recovery. This study highlights G. sulphuraria 009 as a viable source of phycocyanin in POME-based cultivation, offering insights into industrial wastewater valorization and sustainable bioproducts.